Accumulation Studies at a High Elevation Glacier Site in Central Karakoram - Christoph Mayer; Astrid Lambrecht; Hans Oerter; Margit Schwikowski; Elisa Vuillermoz; Nicola Frank; Guglielmina Diolaiuti (Advances in Meteorology)
The precipitation conditions in central Karakoram are investigated on the basis of snow samples from high elevated snow pits at Urdok glacier from 2006 and the analysis of atmospheric transport trajectories in combination with the general, large scale pressure distribution. Our analysis shows that accumulation at the high elevated regions of the central Karakoram is dominated by the west wind circulation (WWC). Incursions of the South Asian monsoon (SAM) occur sometimes during the summer months accompanied by strong precipitation but play a minor role for the total accumulation amount. Dust layers found in the snow pits show a rare earth elements signature which indicates that the dust very likely originates from the arid regions of western China and Central Asia. Our trajectory calculations based on NCEP/NCAR reanalysis data confirm that especially during late spring and early summer the westerly flow is redirected over the Tarim basin to reach central Karakoram from an East/Southeast direction. The preservation of the layer structure and the clear seasonal signals in the snow pits indicate that locations above 5200 m in central Karakoram will be suitable places for retrieving longer climate records from ice cores.